Signs of life : a memoir - Taylor, Natalie (Natalie Kelland) (New York : Broadway Paperbacks, 2012)
Natalie Taylor was leading a charmed life: she had a fulfilling job, a wonderful husband, Josh, a new house, and a baby on the way. Then, while visiting her sister, she gets the news that Josh has died in a freak accident. Four months before the birth of her son, Natalie is leveled by loss. What follows is an unexpected transformation as Natalie calls upon resources she didn't even know she had in order to reimagine and rebuild a life for her and her son.
Originally published in hardcover: New York : Broadway Books, 2011.
Includes a reading group guide.
Keywords: Widows -- United States -- Biography; Loss (Psychology); Bereavement